COMMUNITY EMPOWERMENT BY SCALING UP PAJAMBON VILLAGE GUAVA FRUIT MANAGEMENT THROUGH LOCAL INNOVATIVE DIGITALIZATION & PROCUREMENT OF E-COMMERCE BUMDES - Maryam, Egidia; Febriansyah, Yudi; Nurochmah, Dina (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Pajambon Village is the westernmost village in Kramatmulya District, Kuningan Regency, West Java. Pajambon Village is located in a strategic position because it is in a highland area that has a lot of potential for abundant natural resources. The majority of Pajambon Village residents work as guava farmers and entrepreneurs. Red guava is the leading natural resource of Pajambon Village, but the obstacle faced is that the majority of the Pajambon Village community has not been able to process red guava due to limited human resources, capital, limited marketing scope and lack of response from the local government. Therefore, it is necessary to empower the community to become entrepreneurs who can advance the village economic sector. Based on the environmental conditions above, through the Capacity Building Program of the Accounting Student Association Student Organization (PPK ORMAWA HIMAKU), socialization activities of the Entrepreneurial Village / Village program will be carried out to the community with the Entrepreneurial Village / Village Movement in processing red guava into products that have selling value, with local product innovations, namely guava leaf tubruk tea, Fruity Noodles or red guava fruit processed noodles which have good health benefits, training in packaging and digital-based MSME marketing assistance in collaboration with BUMDES, Pajambon Village MSME Bazaar and Paajambon Village Business Legality Making. It is expected that after the Entrepreneurial Village Movement by holding training and mentoring can improve the quality of human resources (Human Resources) and the productivity of the Pajambon village economy, Making Pajambon Village as an Entrepreneurial Village creates new entrepreneurs who are pioneers in entrepreneurship, so that in the future there can be a new regeneration of sustainable village entrepreneurs.